RCAAP Project - Donato, H (2010)
RCAAP (Repositório Científico de Acesso Aberto de Portugal = Portugal Open Access Science Repository) is an initiative that aims to increase the visibility, accessibility and dissemination of Portuguese research results, to facilitate the access to the information about the Portuguese scientific output, as well as to integrate Portugal in the wide range of international initiatives in this domain. RCAAP is an initiative of UMIC – Knowledge Society Agency, developed by FCCN – National Foundation for Scientific Computation, offering an advanced service on the Portuguese Network of Science and Education (Rede de Ciência e Educação). The project’s execution has the technical and scientific participation of the Minho University. The project is financed by the Programa Operacional Sociedade do Conhecimento and UMIC. RCAAP is the most relevant Portuguese project related with Open Access. The project produced the following deliverables: • RCAAP Portal (http://www.rcaap.pt) which aims to collect, aggregate and index Open Access scientific contents from Portuguese institutional repositories, forming a single entry point for searching, discovery and recall of thousands of scientific and scholarly publications; • SARI (Serviço de Alojamento de Repositórios Institucionais), an ASP service for institutional repositories, allowing institutions to completely “brand” their repositories as desired.